Money, prices and liquidity effects: Separating demand from supply - Jagjit S. Chadha; Luisa Corrado; Qi Sun (University of Kent, Department of Economics, 2008)
In the canonical monetary policy model, money is endogenous to the optimal path for interest rates and output. But when liquidity provision by banks dominates the demand for transactions money from the real economy, money is likely to contain information for future output and inflation because of its impact on financial spreads. And so we decompose broad money into primitive demand and supply shocks. We find that supply shocks have dominated the time series in both the UK and the US in the short to medium term. We further consider to what extent the supply of broad money is related to policy or to liquidity effects from financial intermediation.
Keywords: E32; F32; F41; 330; money; prices; Bayesian VAR identification; sign restrictions; Geldtheorie; Geldangebot; Geldnachfrage; Transaktionskosten; Inflationserwartung; VAR-Modell; Großbritannien; USA